TRANSFORMATIONAL LEADERSHIP AND PROJECT SUCCESS: THE MEDIATING ROLE OF EFFECTIVE COMMUNICATION - Muazam Ali; Farooq Rasheed (International Journal of Contemporary Issues in Social Sciences, 2024)
The study explores the connection between transformational leadership and successful project outcomes, with effective communication proposed as an intermediary factor. Prior research has established a link between transformational leadership and favorable project results, but the underlying mechanisms behind this association remain largely unexplored. This study looks at the mediating function of effective communication to close this gap. Data was collected from 130 construction project managers based in Islamabad, Rawalpindi, and Gilgit, Pakistan. The analysis revealed a significant direct effect of transformational leadership on project success. Moreover, effective communication was found to mediate this relationship partially, indicating that the positive influence of transformational leaders on project outcomes is partially attributable to their ability to communicate effectively with their teams. These findings hold theoretical significance by enhancing our understanding of how transformational leadership fosters project success. The study underscores the importance of transformational leadership style and effective communication for organizations engaged in project-based work. By investing in management training programs that cultivate these critical skills, organizations can enhance their project management practices and ultimately achieve higher rates of project success.